Perfusion quantification using voxel‐wise proton density and median signal decay in PREFUL MRI. Issue 3 (9th April 2021) - Glandorf, Julian; Klimeš, Filip; Behrendt, Lea; Voskrebenzev, Andreas; Kaireit, Till F.; Gutberlet, Marcel; Wacker, Frank; Vogel‐Claussen, Jens
Abstract : Purpose: Contrast‐free lung MRI based on Fourier decomposition is an attractive method to monitor various lung diseases. However, the accuracy of the current perfusion quantification is limited. In this study, a new approach for perfusion quantification based on voxel‐wise proton density and median signal decay toward the steady state for Fourier decomposition‐based techniques is proposed called QQuantified (QQuant ). Methods: Twenty patients with chronic obstructive pulmonary disease and 18 patients with chronic thromboembolic pulmonary hypertension received phase‐resolved functional lung‐MRI (PREFUL) and dynamic contrast‐enhanced (DCE)‐MRI. Nine healthy participants received phase‐resolved functional lung‐MRI only. Median values of QQuant were compared to a Fourier decomposition perfusion quantification presented by Kjørstad et al (QKjørstad ) and validated toward pulmonary blood flow derived by DCE‐MRI (PBFDCE ). Blood fraction maps determined by the new approach were calculated. Regional and global correlation coefficients were calculated, and Bland‐Altman plots were created. Histogram analyses of all cohorts were created. Results: The introduced parameter QQuant showed only 2 mL/min/100 mL mean deviation to PBFDCE in the patient cohort and showed less bias than QKjørstad . Significant increases of regional correlation with PBFDCE were achieved (r = 0.3 vs. r = 0.2, P < .01*). The trend of global correlation toward PBFDCE is not uniform, showing higher values for QKjørstad in the chronic obstructive pulmonary disease cohort than for QQuant and vice versa in the chronic thromboembolic pulmonary hypertension cohort. In contrast to QKjørstad, QQuant perfusion maps indicate a physiologic dorsoventral gradient in supine position similar to PBFDCE with similar value distribution in the histograms. Conclusion: We proposed a new approach for perfusion quantification of phase‐resolved functional lung measurements. The developed parameter QQuant reveals a higher accuracy compared to QKjørstad .